If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2 + -1y) = 3 + -5y (2 * 6 + -1y * 6) = 3 + -5y (12 + -6y) = 3 + -5y Solving 12 + -6y = 3 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 12 + -6y + 5y = 3 + -5y + 5y Combine like terms: -6y + 5y = -1y 12 + -1y = 3 + -5y + 5y Combine like terms: -5y + 5y = 0 12 + -1y = 3 + 0 12 + -1y = 3 Add '-12' to each side of the equation. 12 + -12 + -1y = 3 + -12 Combine like terms: 12 + -12 = 0 0 + -1y = 3 + -12 -1y = 3 + -12 Combine like terms: 3 + -12 = -9 -1y = -9 Divide each side by '-1'. y = 9 Simplifying y = 9
| 8z+12=5z-25 | | 2.25+2.5x=1.10+8.5x | | 5y+23=83 | | -2*x=2 | | 12=c+3 | | 8x+7=-6+2x+25 | | -c+4+8+5c=0 | | 2x-2(4x+5)=-6(x-3)-8 | | 55+2x=117 | | x^2+14x=-x^2+3x+5 | | 8x-102+2x+6=180 | | 6x-68=-x+51 | | -2n-(9-10)= | | 32a^3+8a^2+12a+3= | | -7(6x-9)=-273 | | 16=2-(x-8) | | 7+7x=-(7-7x)+8 | | -6(x+4)=-18-7x | | 1m-5=.4m+4 | | 26x-3=180 | | -2m=6m-9 | | 18+2m=60 | | 3(4g+6)=2(6y+9) | | 4x+14=3+7x-7 | | 1+4(-4+2x)=-15+8x | | -8n+2=3+7n+10 | | 5x-120=13 | | 20+9h=92 | | -3x^2+11x+35=7-4x^2 | | -3p+8=6-(10p+3) | | 11=2+2v+7 | | -15=6x+3(4-3x) |